THE INFLUENCE OF PORT INFRASTRUCTURE ON LOGISTICS PRICES AS A MARITIME AXIS IN BATAM CITY: BATU AMPAR PORT - Yusra Aulia Sari; Mulia Pamadi (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2021)
The city of Batam has a geographical location which is a factor strategic for the port sector, as an activity sector potential and attractive economy prospective, so it needs to be well regulated and integrated with Batam's national spatial planning. One of the biggest goods ports in the city of batam is the Batu Ampar port. The aim of this reserach was to determine The influence of port infrastructure on logistics prices as a maritime axis in Batam City in Batu Ampar Port. This research uses descriptive quantitative approach and secondary data from the Batam port office and the Human Settlements and Spatial Planning Office. The results of this research are Batam national spatial plan for the realization of Batu Ampar as an export-oriented industrial center integrated with port services and trading areas is not compatible with the available port facilities. Batam as a port city still has not prioritized the development of port infrastructure and coastal areas in accordance with the Batam city spatial plan. Problems with the logistics costs in Batam are caused by several things: Inadequate port infrastructure for decades, high shipping costs, which are more expensive than other regions; port loading and unloading facilities that are less than the port standard; opportunities to develop direct calls and untapped transshipment and logistics management at ports that are still being carried out by door-to-door logistics companies in Singapore.